The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.iecr.3c00226
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling of Dyed Polyester Fabrics into Copper-1,4-Benzenedicarboxylate (CuBDC) Metal–Organic Frameworks

Abstract: We report on a pathway to synthesize metal− organic frameworks (MOFs) using discarded textiles as a raw material. Discarded objects made of poly(ethylene terephthalate) (PET) could be an inexpensive and globally available source for 1,4-benzenedicarboxylic acid (H 2 BDC), also known as terephthalic acid, a building block of carboxylate-based MOFs. Previous studies on using discarded PET to synthesize MOFs have mainly focused on PET bottles. In contrast, we demonstrate the use of dyed polyester fabrics as a raw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This indicated that the OCs further occupied more spaces due to their increased functional groups which linked to neighboring functional groups by Tp and thus displaced more Cu 2+ . This phenomenon was confirmed by broad and small DTG curves in the regions of 325 to ∼400 °C and ∼410 to ∼475 °C attributed to the degradation of approximately 40.72 % framework resulting in splitting the organic fragment from the inorganic copper fragments thus forming 3.88 % residual Cu−O [49,35] …”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…This indicated that the OCs further occupied more spaces due to their increased functional groups which linked to neighboring functional groups by Tp and thus displaced more Cu 2+ . This phenomenon was confirmed by broad and small DTG curves in the regions of 325 to ∼400 °C and ∼410 to ∼475 °C attributed to the degradation of approximately 40.72 % framework resulting in splitting the organic fragment from the inorganic copper fragments thus forming 3.88 % residual Cu−O [49,35] …”
Section: Resultsmentioning
confidence: 64%
“…The FTIR spectra of Tp displayed broadband at 1674 cm −1 and 1280 cm −1 attributed to the stretching frequency of C=O, and C−O, respectively while the peaks at 3062 cm −1 and 1417 cm −1 correspond to C−H stretching of the benzene ring and OH in‐plane deformation [35] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…311 More elaborated products were also directly produced from (dyed) PET textiles, such as (MOFs). 312–314…”
Section: Discussionmentioning
confidence: 99%